Psychometric properties of a questionnaire to assess daily peer violence in schools - Fernández Baena, Francisco Javier; Trianes Torres, María Victoria; De la Morena Fernández, María Luisa; Escobar Espejo, Milagros; Infante Cañete, Lidia; Blanca Mena, María J. (Anales de Psicología / Annals of Psychology, 2010)
Problems with peer violence in schools have consequences on the whole education. Its early detection is vitally important in order to design educational programmes and prevent or reduce the negative consequence of violence. This research team has developed a new questionnaire to assess peer violence of both low and moderate intensity. The Daily School Violence Questionnaire (Cuestionario Violencia Escolar Cotidiana, CUVECO) has been created using the California and Safety School Climate Survey as a base, and has been applied to a sample of 954 students in secondary education. The CUVECO shows a stable factorial structure of two variables: experience of suffering violence, and violence observed at school. Reliability and validity analysis reveal satisfactory results. A sex and grade difference analysis is also presented. A higher score for violence suffered was found in boys and in the lower levels of secondary education. Significant differences were not found in the observe violence variable neither sex nor grade. Finally, we discuss the usefulness of this new instrument for the screening assessment of daily peer violence in schools, specifically for their detection and validation of psychoeducational programmes.